Beyond Memorization: Building Problem-Solving Skills in Sequences for Future Math Teachers - Joy M., Notarte Michelle; Lea Rose, Aguilando; Nathaniel D., Larazi; Martin Jr., L., Nobis; Apple Erika B, Acebron (East Asian Journal of Multidisciplinary Research, 2024)
This study looks into how future math teachers solve problems when dealing with sequences. Data show a worrying trend: none of the respondents received a very high score, and more than 60% received a low grade. The biggest obstacle turned out to be harmonic sequences, indicating a critical knowledge gap. Even simple sequences, such as arithmetic sequences, could be challenging, especially when phrased issues and non-consecutive phrases were included. It's interesting to note that students started using online tools like YouTube lessons as part of a self-help movement. This, however, draws attention to a possible over-reliance on outside sources. The study highlights how crucial it is to reinforce fundamental information across a range of sequence types. Future math teachers can approach and solve sequence issues with more confidence if they have a solid grasp of the fundamentals and have conducted purposeful web research. This will ultimately result in more effective teaching methods.